2006
DOI: 10.1093/nar/gkl786
|View full text |Cite
|
Sign up to set email alerts
|

The telomerase-recruitment domain of the telomere binding protein Cdc13 is regulated by Mec1p/Tel1p-dependent phosphorylation

Abstract: The DNA damage-responsive protein kinases ATM and ATR phosphorylate SQ/TQ motifs that lie in clusters in most of their in vivo targets. Budding yeast Cdc13p contains two clusters of SQ/TQ motifs, suggesting that it might be a target of Mec1p/Tel1p (yeast ATR/ATM). Here we demonstrated that the telomerase recruitment domain of Cdc13p is phosphorylated by Mec1p and Tel1p. Gel analysis showed that Cdc13p contains a Mec1/Tel1-dependent post-translational modification. Using an immunoprecipitate (IP)-kinase assay, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
150
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 109 publications
(157 citation statements)
references
References 57 publications
4
150
2
1
Order By: Relevance
“…We previously found that Tel1 and Mec1 phosphorylate Cdc13 at S249 and S255 in vitro 22 . Several laboratories also discovered genetic and physical evidence of the importance of Tel1 in telomerase recruitment [23][24][25] .…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…We previously found that Tel1 and Mec1 phosphorylate Cdc13 at S249 and S255 in vitro 22 . Several laboratories also discovered genetic and physical evidence of the importance of Tel1 in telomerase recruitment [23][24][25] .…”
Section: Discussionmentioning
confidence: 94%
“…1a) [22][23][24][25][26][27] . To examine the possibility that recruitment of telomerase by Cdc13 may be repressed by phosphatases, we determined the phosphorylation level of Cdc13 throughout the cell cycle for wild type (WT) and various phosphatase deletion strains.…”
Section: Pp2a Dephosphorylates Cdc13 Serine 249 and 255mentioning
confidence: 99%
See 3 more Smart Citations